x:\(\left(-2\dfrac{1}{15}\right)+3\dfrac{1}{2}=-\dfrac{3}{4}\)
<=> x : \(\left(-2\dfrac{1}{15}\right)\) = \(\dfrac{-3}{4}-3\dfrac{1}{2}\)
<=> x = \(\dfrac{-17}{4}\) . \(\left(-2\dfrac{1}{15}\right)\)
<=> x = \(\dfrac{527}{60}\)
\(x:\left(-2\dfrac{1}{15}\right)=-\dfrac{3}{4}-3\dfrac{1}{2}\)
\(x:\left(-2\dfrac{1}{15}\right)=-\dfrac{3}{4}-\dfrac{7}{2}\)
\(x:\left(-2\dfrac{1}{15}\right)=\dfrac{-3-14}{4}\)
\(x:\left(-2\dfrac{1}{15}\right)=\dfrac{-17}{4}\)
\(x=\dfrac{-17}{4}.\left(-\dfrac{31}{15}\right)\)
\(x=\dfrac{527}{60}\)